UPAYA PENINGKATAN HASIL BELAJAR PESERTA DIDIK FASE E1 MELALUI MODEL TWO STAY TWO STRAY (TSTS) DALAM PEMBELAJARAN SOSIOLOGI DI SMAN 1 KEC. KAPUR IX - Fitri Enjelika; Hefni; Yanti Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning outcomes of Phase E1 students in sociology at SMAN 1, Kapur IX District. The purpose of this study was to improve student learning outcomes through the Two Stay Two Stray (TSTS) model.The research method used was Classroom Action Research (CAR) as formulated . The theory used in this study is Cognitivism. The data from this study consisted of information about actions obtained from interviews, observations, observations of teacher activities, observations of student activities, and pre- and post-tests of student learning outcomes.The results of the cycle 1 research obtained an average student score of 68.71 with 7 students (21.87%) completing the course and 25 students (78.12%) not completing it. In cycle 2, the average student score was 81.34 with 23 students (71.87%) completing the course and 28.12% not completing the course. In cycle 3, the average student score was 91.40 with 31 students (96.87%) completing the course and 1 student (3.12%) not completing the course. This means that in cycle 3 this research has been achieved. Based on the research that has been done, it can be concluded that the application of the Two Stay Two Stray (TSTS) model in sociology learning can improve student learning outcomes, namely from 21.87% in cycle 1 increasing to 71.87% in cycle 2, and increasing again to 96.87% in cycle 3.